2018
DOI: 10.5380/rvx.v13i2.59166
|View full text |Cite
|
Sign up to set email alerts
|

Formação De Professores Em Uma Comunidade De Prática: O Caso Do Nucli Inglês Sem Fronteiras Na Ufpr

Abstract: Este artigo tem por objetivo descrever as práticas de um grupo de alunos-professores do Núcleo de Língua Inglesa (NucLi Inglês) do Programa Idiomas sem Fronteiras da Universidade Federal do Paraná (IsF – UFPR), refletindo sobre como os membros desse grupo apresentam, em suas práticas, engajamento mútuo, empreendimento conjunto e um repertório compartilhado, caracterizando-o como uma Comunidade de Prática (CP), e como as interações e participação dos membros na comunidade promovem a aprendizagem e a trans/forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…teachers of the language. In our view, this possible interpretation is strengthened when we take two factors into account: a) the fact that previous reports about native-speakerism among experienced teachers in Brazil showed a prevalence of feelings of imposture (Diniz de Figueiredo, 2011;Rajagopalan, 2005); and b) the growth in teacher education courses, classes and other initiatives that specifically try to address native-speakerism (e.g., Walesko, 2019) with the aim of empowering students, using, for example, decolonial perspectives and virtual exchange to connect and support L2 teachers (Wimpenny et al, 2022).…”
Section: Understanding Emotions Of Pre-service Teachers In a Brazilia...mentioning
confidence: 76%
“…teachers of the language. In our view, this possible interpretation is strengthened when we take two factors into account: a) the fact that previous reports about native-speakerism among experienced teachers in Brazil showed a prevalence of feelings of imposture (Diniz de Figueiredo, 2011;Rajagopalan, 2005); and b) the growth in teacher education courses, classes and other initiatives that specifically try to address native-speakerism (e.g., Walesko, 2019) with the aim of empowering students, using, for example, decolonial perspectives and virtual exchange to connect and support L2 teachers (Wimpenny et al, 2022).…”
Section: Understanding Emotions Of Pre-service Teachers In a Brazilia...mentioning
confidence: 76%
“…The coordinators had to be tenured professors from LwB participating universities. A number of previous studies have reported the importance of the LwB as a teacher development program (HAUS, 2015;AUGUSTO-NAVARRO;GATOLLIN, 2016;KIRSCH;WALESKO;KLUGE;ALMEIDA, 2016;WELP;FONTES;.…”
Section: Introductionmentioning
confidence: 99%
“…(WALESKO; FELIX, 2018, p. 70) Assim, o aprendizado através de interações, reflexões e práticas colaborativas contribui para a constituição de identidades dos participantes. As autoras caracterizam o NucLi como uma comunidade de prática para professores em formação que "[...] incentiva no aluno-professor o desenvolvimento do pensamento crítico-reflexivo e a capacidade de aplicar teorias à suas práticas, bem como de teorizar suas práticas e produzir conhecimento informado" (WALESKO;FELIX, 2018, p. 67).…”
unclassified